Building climate resilience in the Ethiopian pastoral and agro-pastoral region: Impact of the livestock water and pasture monitoring and early warning system - Tegegne, Getachew; Alemayehu, Sintayehu; Workeneh, Sintayehu; Tesfaye, Lidya; Gebre, Liyuneh; Abdulhamid, Numery; Girvetz, Evan (Bioversity International and International Center for Tropical Agriculture, 2025)
Ongoing droughts have a profound impact on agricultural productivity, especially in regions of Ethiopia that rely heavily on livestock and crops. Climate change is making these challenges even worse. To help combat this issue, early warning systems are essential as they provide timely alerts and actionable information to minimize the effects of drought. Alliance Bioversity International and CIAT developed a User-Centered Livestock Water and Pasture Monitoring and Early Warning System (LWPM-EWS) designed to bolster the resilience of pastoralists and agro-pastoralists. An analysis conducted after implementation revealed that an impressive 99% of key informants utilized the LWPM-EWS for making important decisions about water management, grazing, and crop irrigation. The system has made it easier for communities to access water and pasture, reduced livestock losses, and encouraged collaboration among community members. About 80% of respondents indicated a reduction in conflicts over resources since the project's implementation. Furthermore, 84% noticed increased engagement from humanitarian organizations, which has led to greater support overall. Furthermore, 93% of key informants reported that the LWPM-EWS project significantly improved the community's ability to handle droughts and other climate-related challenges, showcasing its transformative impact on building resilience in Borana, Ethiopia.